Investigation of molecular design, synthesis, and biological assessment of new benzopyran derivatives - Agasa Ramu, Mahesh; Metri, Somashekhar; A Hunnura, Trupti; Patil, Koushallya; B Sannakki, Hanamant (Journal of Applied Pharmaceutical Research, 2025)
Background: Tuberculosis (TB) remains a global health challenge, necessitating the discovery of novel anti-tubercular agents. The N-(8-hydrazinyl-3,4-dihydro-2H-1-benzopyran-6-yl)-N'-phenyl urea (HSM-II) scaffold has shown potential in developing effective drug candidates. Objective: This study aimed to design and evaluate 50 derivatives of HSM-II for their anti-tubercular activity, focusing on compounds demonstrating strong interactions with the protein PKS13 (PDB ID: 5v3y). Methods: A series of derivatives was synthesized, starting with the reaction of 8-bromo-3,4-dihydro-2H-1-benzopyran-6-amine and phenyl carbamic acid, yielding six new benzopyran derivatives. These were further treated with various aromatic halides to produce the HSM-II derivatives. Molecular docking studies were performed to identify compounds with high binding affinity to PKS13. Promising candidates (HSM-II-3, HSM-II-13, HSM-II-27, HSM-II-33, HSM-II-42, and HSM-II-49) were selected for biological evaluation. Anti-tubercular activity was assessed in vitro using the Alamar Blue Susceptibility Test (MABA) against Mycobacterium tuberculosis H37Rv and H37Ra strains. Results: Docking studies revealed high binding scores for the selected compounds, indicating strong interactions with the target protein. In vitro evaluations demonstrated significant anti-tubercular activity for the majority of synthesized derivatives. The pharmacologic profile of the compounds suggests potential as lead candidates for further optimization. Conclusion: This study presents the design, synthesis, and biological evaluation of 50 diverse derivatives of N-(8-hydrazinyl-3,4-dihydro-2H-1-benzopyran-6-yl)-N'-phenyl urea (HSM-II). Six derivatives (HSM-II-3, HSM-II-13, HSM-II-27, HSM-II-33, HSM-II-42, and HSM-II-49) demonstrated high binding affinities with PKS13 (PDB ID: 5v3y), with scores reaching -11.4 kcal/mol, and potent in vitro anti-tubercular activity, as assessed using the Alamar Blue Susceptibility Assay (MABA). Prominent derivatives exhibited MIC values significantly lower than those of standard drugs like rifampicin.